2022
DOI: 10.1186/s12888-021-03673-6
|View full text |Cite|
|
Sign up to set email alerts
|

Childhood trauma and current depression among Chinese university students: a moderated mediation model of cognitive emotion regulation strategies and neuroticism

Abstract: Background Childhood trauma (CT) is considered as a highly risk factor for depression. Although the pathway of CT to depression, especially the mediating or moderating effects of cognitive emotion regulation strategies (CERS) or neuroticism, have investigated by several studies, the results were inconsistent and there is a paucity of full models among these interactive factors. This study aims to examine the relationships among CT, adaptive / maladaptive CERS, neuroticism, and current depressio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 62 publications
0
7
0
Order By: Relevance
“…It is very likely that, due to immaturity, they fail to resolve these adverse situations or resolve them at a high emotional cost, which leads to the development of a diminished and questioned self-image; this damage to the self can become a secondary stressor that affects development and threatens well-being in adulthood [ 45 ]. Reasons why this effect of early adverse experiences is said to be direct in early adulthood: research with university students has shown that this population has a special cognitive vulnerability; they would have a deficit in their cognitive emotional regulation strategies, which can moderate the impact of early trauma on a current depression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is very likely that, due to immaturity, they fail to resolve these adverse situations or resolve them at a high emotional cost, which leads to the development of a diminished and questioned self-image; this damage to the self can become a secondary stressor that affects development and threatens well-being in adulthood [ 45 ]. Reasons why this effect of early adverse experiences is said to be direct in early adulthood: research with university students has shown that this population has a special cognitive vulnerability; they would have a deficit in their cognitive emotional regulation strategies, which can moderate the impact of early trauma on a current depression [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, particularly in young adulthood (18 to 23 years old), an increase in these trauma-associated depressive symptoms has been observed; its effect is considered direct at this age before later stages of adulthood in which various stressors may interfere ([ 16 ]). Furthermore, the literature describes the mediating role of cognitive emotion regulation strategies in this relationship, particularly in university students ([ 17 , 18 ]).…”
Section: Introductionmentioning
confidence: 99%
“…In college students, previous studies (Tao et al, 2021;Wang et al, 2020) indicated that childhood trauma is correlated with the risk of depression, and some studies (Chu et al, 2022;Li et al, 2021;Mall et al, 2018) further found that childhood trauma could predict depression. For the mechanism of this effect, some studies (Hammen et al, 2000;Kendler et al, 2004;LeMoult et al, 2020) found that individuals who experienced trauma were more sensitive to future adversity or negative events, and thus, some minor events may also trigger their depressive reactions.…”
Section: Introductionmentioning
confidence: 99%
“…In this study, the Childhood Trauma Questionnaire-Short Form (CTQ-SF), the Emotional Regulation Questionnaire (ERQ), and the Patient Health Questionnaire-9 (PHQ-9) were used to examine the childhood trauma, cognitive emotion regulation mechanisms, and depressive symptom of teenagers individually. Compared to earlier investigation on mediation analysis of cognitive emotion regulation strategies, in which they are derived for these two regulation strategies ( 34 ), We measured the Zhuang adolescents' experiences of childhood trauma using the widely established CTQ-SF scale; another research utilized the CTQ scale but evaluated it exclusively from the standpoint of emotional and physical abuse ( 35 ). Moreover, little research has sought to simultaneously analyze cognitive emotion regulation strategies' mediating and moderating effects on the relationship between depressive symptom and childhood trauma in Chinese Zhuang adolescents.…”
Section: Introductionmentioning
confidence: 99%